A comparison of rates of time averaging between the bivalve Macoma cleryana and brachiopod Bouchardia rosea on a shallow subtropical shelf - Barbour-Wood, S. L.; Krause R.A, Jr.; Kowalewski, M.; Wehmiller, J. F.; Simoes, M. G.; Goodfriend, G. A. (Geological Society of America, Abstracts with Programs, 2003)
35(6):273
id: 720